Implementation of Clinical Pharmacy Services for Inpatients with Improvement Strategies Based on SWOT Analysis - Muhammad Aisy Akbar Firdaus; Wiwin Herdwiani; Tri Wijayanti (Indonesian Journal of Global Health Research, 2025)
Pharmaceutical Service Standards in Hospitals are regulated in the Regulation of the Minister of Health of the Republic of Indonesia Number 72 of 2016 on the management of pharmaceutical preparations, medical devices, and consumable medical materials as well as clinical pharmacy services in carrying out pharmaceutical service duties in hospitals. This study aims to evaluate the implementation of clinical pharmacy services in inpatients Hospital X in Surakarta and propose improvement strategies through SWOT analysis. The research method used is quantitative descriptive with a retrospective design. Samples were obtained by purposive sampling technique with pharmacist respondents who were directly responsible for clinical pharmacy services to and inpatient patients. The data analysis used was a validity and reliability test and improvement strategies using SWOT analysis. The results of the study show that clinical pharmacy activities are relatively good except for monitoring drug levels in the blood which have not yet been implemented. It is concluded that the implementation of clinical pharmacy services in inpatients at Hospital X is classified as a good category with a percentage (74%) and is in accordance with PMK No. 72 of 2016 except the unimplemented drug therapy level monitoring. The results of the SWOT analysis of IFAS with a positive result of 0.95 and a positive effas of 0.48 so that the position of the hospital's pharmaceutical installation is in quadrant I so that the right strategy is an aggressive strategy.